Designing a Strategic Talent Management Framework to Cultivate Digital Talent in PT INTI (Persero) - Syafira Annisa Azzahra; Hari Nugraha; Teni Listiani; Nadiarani Anindita (Innovation Business Management and Accounting Journal, 2025)
PT INTI (Persero) is a company driven by a mission, with one pivotal objective being the cultivation of digital talent to fortify the industry and ecosystem. In pursuit of this mission, the imperative of instituting an effective talent management system at PT INTI (Persero) becomes evident. However, the reality stands that the company has not yet fully realized the implementation of an optimal talent management system. In light of this, the present study delves into an analysis of the stages of PT INTI (Persero)'s talent management system, aimed at identifying the obstacles impeding its full execution and devising a prospective talent management framework suitable for PT INTI (Persero). Employing qualitative methodologies, this research employs data gathering techniques inclusive of interviews, observations, and document reviews. The findings from this investigation reveal the absence of established procedures or regulations governing the implementation of the talent management system at PT INTI (Persero). Based on these conclusions, a well-crafted design for the talent management system has been formulated, tailored to the specific field conditions and incorporating ongoing and forthcoming programs envisioned by PT INTI (Persero). This comprehensive design encompasses six distinct stages: talent acquisition, talent training and development, talent deployment, talent performance management, talent retention, and talent release.